Gênese e mutações dos papéis de editor no Maranhão das casas tipográficas às edições estatais - SILVA, Franklin Lopes (2021)
ABSTRACT In this thesis we analyze the processes of institution of the social role of editor, its genesis, conditions of action and mutations in the "maranhense" context, taking as reference the period between the second half of the nineteenth century, which covers the "glorious phase" of literary "local" production, going through its phase of "decay" in the first half of the twentieth century and resumed with the concentration on editorial investments promoted by public bodies. This is an investigation about the historical processes of social differentiation around this category and the investments made around these moments, in the collective and individual planes. More specifically, in the Maranhão context, the editor's figure would be a kind of manager of symbolic investments operated through writing by agents who worked on several fronts and linked to very diverse instances (public bodies linked to culture, political parties, literary groups, etc.). Due to the low degree of institutionalization of editorial dynamics in this state, which is apparent in the ephemerality of editorial companies and the almost absence of editorial competition between companies and their catalogs - generally understood as instruments of disputes in competitive editorial contexts - catalographic data were compiled from varied sources and scattered among newspapers, public reports , almanacs, interviews, biographies, interviews, etc. From them we invested in systematizations that allowed us to verify some variations and constancy in the types of editorial investments operated and their respective instances throughout the period under discussion. This also justifies the importance of the social relations identified in this research and how much such characteristics affect the possibilities of displacement sand transits of agents operated in this editorial space. The allocations of agents who invest in writing in this context are therefore closely related to the possibilities of personal paybacks and in the loyalty mediated by reciprocity around editorial dynamics. This implies the understanding that the structuring bonds of social life are imposed through the mediation of networks of relationships that connect social segments and individuals. In this step, the agents recognized under the roles of "editor" perform, through their activities of production and bibliographic publication, a kind of "alchemy of the gift", transmuting them into entry and permanence passwords on the edges (we will see that it is necessary to build up investments in various areas and domains of action to reach the most prominent posts) of the elitized circles of "Maranhão intellectuality" always with their eyes turned to the center.